Protocol for a living systematic review for the management of concussion in adults - Mark Bayley; Diana Velikonja; Shawn Marshall; Alexander Lithopoulos; Dorothyann Curran; Lisa Fischer; Christopher Knee; Julia Lauzon; Margaret Nevison (BMJ Open)
Introduction Concussion/mild traumatic brain injury (mTBI) often presents initially with disabling symptoms that resolve, but for an unfortunate minority some of these symptoms may become prolonged. Although research into diagnosis and interventions for concussion is increasing, study quality overall remains low. A living systematic review that is updated as evidence becomes available is the ideal research activity to inform a living guideline targeting clinicians and patients. The purpose of this paper is to present the protocol of an ongoing living systematic review for the management of adult concussion that will inform living guidelines building off the Guideline for Concussion/Mild Traumatic Brain Injury and Persistent Symptoms: third Edition.Methods and analysis The Preferred Reporting Items for Systematic Review and Meta-Analysis Protocol guidelines were followed in the reporting of this systematic review protocol. We are including English peer-reviewed observational studies, trials, qualitative studies, systematic reviews and clinical practice guidelines related to diagnosis/assessment or treatment of adult concussion. Future searches will be conducted at minimum every 6 months using the following databases: MEDLINE ALL, EMBASE, Cochrane, PsycInfo and CINAHL. The data are managed in the Covidence website. Screening, data extraction and risk-of-bias assessments are being done through multiple raters working independently. Multiple validated tools are being used to assess risk of bias, and the tool applied matches the document or study design (eg, Downs and Black Scale for healthcare interventions). Many concussion experts in various clinical disciplines from across North America have volunteered to examine the evidence in order to make recommendations for the living guidelines.Ethics and dissemination No ethical approval is necessary because primary data are not collected. The results will be disseminated through peer-reviewed publications and on the living guidelines website once built.PROSPERO registration number CRD42022301786.